LEARNING DIFFICULTIES IN SOLVING CALCULUS TESTS - Sumardin Raupu; Siti Zuhaerah Thalhah; Lisnasari Andi Mattoliang (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Calculus is a branch of mathematics that is applied to solve various problems in various fields of science such as engineering, physics, medicine, chemistry, economics, and various other sciences. However, most students assume that calculus is an elusive material. Therefore, it is necessary to have a study of the difficulties of students in solving calculus questions, given the very importance of this concept in taking the next course. This study is qualitative descriptive research that involved forty-two second semester students of the Mathematics Education Program of IAIN Palopo, and six of them are the interview subjects. In data collection, it used written tests and interviews. Furthermore, the data obtained are then analyzed through reduction, data presentation, and conclusions withdrawal. The findings show that the students get learning difficulties in reading by 52.38%, in writing by 66.67%, and in accounting by 57.14%. The factors causing these difficulties, namely students are not able to identify questions, difficulties in using integral symbols, difficulties in using proper techniques and formulas, difficulties in understanding the steps to solve partial integral problems, difficulties in calculations, difficulties in solving until the final stage of the integral process.